The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2147/dddt.s210511
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dexmedetomidine Attenuates Neuroinflammation In LPS-Stimulated BV2 Microglia Cells Through Upregulation Of miR-340</p>

Abstract: BackgroundDexmedetomidine (Dex) was reported to exhibit anti-inflammatory effect in the nervous system. However, the mechanism by which Dex exhibits anti-inflammation effects on LPS-stimulated BV2 microglia cells remains unclear. Thus, this study aimed to investigate the role of Dex in LPS-stimulated BV2 cells.MethodsThe BV2 cells were stimulated by lipopolysaccharides (LPS). BV2 cells were infected with short-hairpin RNAs targeting NF-κB (NF-κB-shRNAs) and NF-κB overexpression lentivirus, respectively. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 45 publications
(44 reference statements)
4
56
0
Order By: Relevance
“…Taken together, LMTK2 overexpression reduced the levels of iNOS, COX-2 and pro-inflammatory factors, TNF-α, IL-1β and IL-6, but increased IL-10 level; possibly due to the dependence of LPS-induced microglia on Nrf2 pathway. However, no significant changes were observed in IL-10 levels following LPS stimulation, which was consistent with a previous report (34). IL-10 is an important inflammatory suppressor in vivo and can inhibit the release of pro-inflammatory cytokines in microglia cells in the central nervous system (35).…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, LMTK2 overexpression reduced the levels of iNOS, COX-2 and pro-inflammatory factors, TNF-α, IL-1β and IL-6, but increased IL-10 level; possibly due to the dependence of LPS-induced microglia on Nrf2 pathway. However, no significant changes were observed in IL-10 levels following LPS stimulation, which was consistent with a previous report (34). IL-10 is an important inflammatory suppressor in vivo and can inhibit the release of pro-inflammatory cytokines in microglia cells in the central nervous system (35).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the results in the rat ICH model, miR-340-5p was detected to be downregulated in the cells treated with LPS. In addition, overexpression of miR-340-5p eliminated the effect of LPS on the secretion of proinflammatory cytokines, which was consistent with the previous evidence [23]. This evidence suggested the anti-inflammatory effect of miR-340-5p on ICH-induced brain injury in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, neuroinflammation is regarded as a pivotal target for ICH treatment. miR-340-5p has been proposed to exert an anti-inflammatory effect in several human diseases [23, 24]. As Gao et al suggested, overexpression of miR-340-5p could suppress inflammatory response as well as the production of IL-1β, TNF-α, and IL-6 in the model of chronic constriction injury [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dexmedetomidine has been widely used as an adjuvant of general anesthesia in patients undergoing cardiac and major non-cardiac surgeries or as a sedative in severe patients in ICU owing to its pharmacological functions of sedation, analgesia, anti-inflammation, and antioxidation [39][40][41]. The dexmedetomidine infusion in this study will begin between the completion of central venous catheterization and the onset of surgery and be maintained until the end of surgery.…”
Section: Discussionmentioning
confidence: 99%